PEMBELAJARAN KONSEP LUAS DAERAH BANGUN DATAR 01 SD DENGAN PENDEKATAN KONSTRUKTIVISTIK Abstract PADA MAHASISWA PGSD - P.Sarjiman P.Sarjiman (LPMPP Universitas Negeri Yogyakarta, 2008)
This study aims to: (1) improve students' understanding of the concept of planefigure areasand how to teach the concept in elementary schools, and (2) investigatestudents' responses to the learning model. This study employed the action researchmodel using the qualitative approach. The qualitative data were analyzed using theinterpretative qualitative techniqueand the quantitative data were analyzed usingthe descriptive statistics. The research subjects were all students in Class Q ofSemester III011 PGSO UPP II, consisting of 42 students. The learning process usingthe· constructivismapproach through this action research comprised three cycles;the first cycle consisted of one meeting, the second cycle two meetings, and· thethird cycle one meeting.In the first cycle, the results were still disappointing; theaverage score was only 54. In the second cycle the average score was 67 and in thethird cycle the average scorewas 79. Similarly, in the first cycle students' responsesand classroom management were still out of control. In the second cycle they werealso still beyond expectation. However, in the third cycle stud·ents' responses andenthusiasms were good as expected. The results of the final test at the end of theaction were higher than the criteria. In addition, students' learning varieties weregood. The learning process employing the constructivism approach can-be used asa learning alternative especiallyin understanding mathematical ·concepts inelementary schools